2014
DOI: 10.3390/w6020196
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Monthly Daily Extreme Water Levels in the St. Lawrence River at the Sorel Station from 1912 to 2010

Abstract: Abstract:Although climate models predict that the impacts of climate change on the temporal variability of water levels in the St. Lawrence River will be seasonally-dependent, such a seasonal effect on the current variability of extreme water levels has never been analyzed. To address this, we analyzed the temporal variability of three hydrological variables (monthly daily maximums and minimums, as well as their ratio) of water levels in the St. Lawrence River measured at the Sorel station since 1912, as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…These low flows may have been caused by the El Niño event (2009–2010), which led to a shortage of soil water, such that more water was required the following year (2010) to recharge the soil. This finding suggests a positive correlation between La Niña events and flows downstream from the reservoir and is consistent with many findings from natural rivers (e.g., Anctil & Coulibaly, ; Assani et al, ; Assani et al, ; Assani et al, ; Assani et al, ; Beauchamp et al, ; Biron et al, ; Coulibaly & Burn, ; Guerfi, Assani, Mesfioui, & Kinnard, ; Mazouz et al, , ; Shabbar, ). Indeed, La Niña events are generally associated with relatively high snowfall in Quebec, which leads to much higher spring flows when this snow melts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These low flows may have been caused by the El Niño event (2009–2010), which led to a shortage of soil water, such that more water was required the following year (2010) to recharge the soil. This finding suggests a positive correlation between La Niña events and flows downstream from the reservoir and is consistent with many findings from natural rivers (e.g., Anctil & Coulibaly, ; Assani et al, ; Assani et al, ; Assani et al, ; Assani et al, ; Beauchamp et al, ; Biron et al, ; Coulibaly & Burn, ; Guerfi, Assani, Mesfioui, & Kinnard, ; Mazouz et al, , ; Shabbar, ). Indeed, La Niña events are generally associated with relatively high snowfall in Quebec, which leads to much higher spring flows when this snow melts.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have looked at this influence on natural rivers in many parts of the world (e.g., Amarasekera, Lee, Williams, & Eltahir, ; Cayan, Redmond, & Riddle, ; Chiew, Piechota, Dracup, & McMahon, ; Chiew & McMahon, ; Clark, Nnaji, & Huang, ; Dilley & Heyman, ; Mosley, ; Piechota, Dracup, & Fovell, ; Räsänen & Kummu, ; Ward, Beets, Bouwer, Aerts, & Renssen, ; Ward, Eisner, Flörke, Dettinger, & Kummu, ; Ward et al, ; Veldkamp et al, 2015). For Quebec more specifically, many studies looked at the relationship between streamflow and ENSO events (e.g., Anctil & Coulibaly, ; Assani, Charron, Matteau, Mesfoui, & Quessy, ; Assani, Landais, Mesfioui, & Matteau, ; Assani, Landry, Labrèche, Frenette, & Gratton, ; Assani, Landry, & Laurencelle, ; Beauchamp, Assani, Landry, & Massicotte, ; Biron, Assani, Frenette, & Massicotte, ; Coulibaly & Burn, ; Mazouz, Assani, Quessy, & Légaré, ; Mazouz, Assani, & Rodriguez, ). These studies have shown that the influence of ENSO on streamflow is relatively weak or nonexistent depending on the type of flow analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Climate index series were produced using the same approach as water level series. The five climate indices which are known to affect the temporal variability of hydroclimatic variables (temperature, precipitation, streamflow, and water levels) in Quebec and North America [e.g., Assani et al ., ; Anctil and Coulibaly , ; Coulibaly and Burn , ; Curtis , ; Déry and Wood , ; Enfield et al ., ; Kingston et al ., ; McCabe et al ., ; Sutton and Hodson , ] were selected. These indices are AMO (Atlantic Multi‐decadal Oscillation), AO (Arctic Oscillation), NAO (North Atlantic Oscillation), PDO (Pacific Decadal Oscillation), and SOI (Southern Oscillation Index).…”
Section: Methodsmentioning
confidence: 99%
“…For safety of lives and property from risks related to floods, proper planning of relevant applications is important for development [1][2][3][4][5][6][7][8][9][10][11][12][13]. To date, dams have become numerous and have had a profound effect on social and economic development.…”
Section: Introductionmentioning
confidence: 99%